2001
DOI: 10.1007/s003300000682
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided obturator nerve block for diagnosis and treatment of painful conditions of the hip

Abstract: Obturator nerve blocks (ONB) have been performed by anaesthesiologists mainly to eliminate the obturator reflex during transurethral resections. An effect on hip pain has also been described. However, being a time-consuming and operator-dependent procedure if performed manually, it has not been widely used for chronic hip pain. The purpose of this pilot study was to check whether CT guidance could improve reproducibility of the block (= immediate effect) and to test its potential value for treatment of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 4 publications
0
28
0
3
Order By: Relevance
“…We consider CT guidance with or without external laser marker systems essential for the effectiveness and safety of interventional procedures, especially in complicated structures such as the SIJ, the spine, the hip joint, or for sympathectomies and diagnostic biopsies [19,20,21,22]. Additional safety is achieved by the close communication with the nonsedated patient during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We consider CT guidance with or without external laser marker systems essential for the effectiveness and safety of interventional procedures, especially in complicated structures such as the SIJ, the spine, the hip joint, or for sympathectomies and diagnostic biopsies [19,20,21,22]. Additional safety is achieved by the close communication with the nonsedated patient during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other trials have previously investigated the effect of an ONB on other painful conditions in the hip joint: ONB guided by CT provided pain relief in 11 of 15 patients with osteoarthrosis, femoral head necrosis, developmental dysplasia, as well as pain following hip arthroplasty in a prospective observational study 20. Another retrospective observational study found pain relief in patients with chronic hip pain after nerve blocks of the articular branches of both the obturator and the femoral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Heywang-Köbrunner et al performed CT-guided obturator nerve blockage for 15 patients with hip pain and cited that this method might be used for diagnosis and treatment for patient with hip pain (26). House et al performed CT-guided obturator blockage technique by using posterior approach for 51 patients.…”
Section: Prevention Of Obturator Reflexesmentioning
confidence: 99%